Evaluasi Sediaan Ekstrak Etanol Daun Sawi Langit (Cyanthillium cinereum (L) H.Rob) Sebagai Formulasi Krim Alas Bedak - Tambunan, Ika Julianti; Sudewi, Sudewi; Nasyabila, Aura (Journal of Pharmaceutical and Health Research, 2025)
Sky mustard leaf (Cyanthillium cinereum (L.) H.Rob) is a herbaceous plant that is used as a natural medicine in the community, especially in the treatment of irritation, intestinal diseases and febrile diseases. Sky mustard leaves are known to contain secondary metabolites such as flavonoids, alkaloids, saponins, tannins, phenolics and triterpenoids. Foundation cream is very popular among women as a powder base during the process of using makeup on the face but few foundation creams use natural ingredients compared to synthetic ingredients. This study aims to determine whether sky mustard leaf extract can be formulated in a foundation cream preparation that at certain doses has antioxidant activity and does not irritate facial skin. The sample used was sky mustard leaves, the research stages began, plant identification, ethanol extract preparation, phytochemical screening, selection of standard formulas, making foundation cream preparations with concentrations of 1%, 1.5%, 2%, blank physical quality assessment of preparations and antioxidant activity tests are some of the tests carried out. The results of this study indicate that the leaves of sky mustard (Cyanthillium cinereum (L.) H.Rob) The foundation cream preparation is homogeneous, stable and has an oil-in-water (M/A) emulsion type. The cream has a pH of 5.7-5.9 after cycle testing and can be applied up to 5-7 cm with an increase in moisture content of 36.86 which is included in the “moist” category, 2% preparation (F3) is the most preferred preparation, the IC50 value of the mustard leaf extract foundation cream formulation is in the “strong” category of 63.08 ppm “very strong” 47.37 ppm at a concentration of 1%, 1.5%. So it is concluded that mustard leaf extract IC50 value is in the “very strong” category of 14.75 ppm. The IC50 value of mustard leaf extract including the “very strong” category is 14.75 ppm. so it can be concluded that sky mustard leaves can be formulated as a foundation cream preparation without irritation.